Answer:
(x - 2)(x + 2)
Explanation:
(x - 2)(x + 2) = x² - (2)² [Since (a - b)(a + b) = a² - b²]
= x² - 4
There are two terms in this expression. Therefore, the give term is a binomial.
(2x - 1)(x + 4) = 2x(x + 4) - 1(x + 4) [Distributive property]
= 2x² + 8x - x - 4
= 2x² + 7x - 4
There are three terms in this polynomial. Therefore, the given polynomial is a trinomial.
(x + 4)(x + 1) = x(x + 1) + 4(x + 1)
= x² + x + 4x + 4
= x² + 5x + 4
This polynomial is having 3 terms therefore, it's a trinomial.
(m - 4)(m + 1) = m(m + 1) - 4(m + 1)
= m² + m - 4m - 4
= m² - 3m - 4
Therefore, this polynomial is a trinomial.
Since (x - 2)(x + 2) is a binomial, so this expression doesn't belong to this group.